Pengembangan Aplikasi Monitoring Kesehatan Ibu Hamil dan Anak Terintegrasi - Ardia Regita Pramesti; Denny Sagita Rusdianto; Heru Nurwarsito (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Parents awareness in giving active immunizations to children in fact is still quite low. Based on data from Ministry of Health, it shows that in 2014 to 2016 there were about 1.7 million children in Indonesia who have not been immunized yet or their status of immunization is still incomplete. Based on the problems above, this document will be discus about the development of system that could provide a notification feature of immunization schedule and also could provide a monitoring feature both on the pregnancy growth and the child growth. The development of this system in total has 46 functional recruitments and 1 non-functional recruitment. System on admin side developed using waterfall life cycle and implemented using CodeIgniter framework with PHP programming language and MySQL as the database. While system on user side who are the expectant mother and the mother of the child that registered under puskesmas implemented using Android. The test result carried out by black box testing and white box testing show that all functional system can run properly, which is valid in all test cases. Whilst the compatibility test show that system can run on 7 different platform.